DEFENSE LAWYERS’ DISCURSIVE STRATEGIES OF CONTROLLING THE LANGUAGE OF THE WITNESSES: QUESTIONING FORMS AND FUNCTIONS IN SOME CRIMINAL COURTS OF OROMIA REGIONAL STATE, ETHIOPIA - BATU BALCHA, Ejarra (Comparative Legilinguistics, 2015)
In everyday conversation the questioners and answerers are in an approximately symmetrical relationship that questioners do not have the information that they are requesting and the answerers are not obliged to answer. On the contrary, in the rule and role governed courtroom question/answer dyad, lawyers usually have particular version of events to control the language of the respondents where witnesses are compelled to respond, and do not have the right to question. So, it may hold back the production and interpretation of the evidence, and consequently hinder the execution of the tasks of the court trial. Such types of courtroom language-related problems are unexplored by academic research in Oromia Regional State. In this regard, no or little is known about these courtroom language-related problems in the criminal courts of the region. In an attempt to fill-in the existing gap, this study investigates how widespread such courtroom linguistic problems are and contribute to the limited conceptual and methodological values of linguistic analysis of courtroom oral discourse in legal institutions of the region. The analysis of this study is based on the authentic, naturally occurring courtroom defense lawyers-witnesses dyad of some Oromia Regional State Criminal Courtrooms. The aim of the study is, therefore, to present the discursive strategies of defense lawyers questioning forms and functions in their attempts to deconstruct persuasive testimony. In so doing, based on the way in which lawyers exploit the specialized speech-exchange linguistic system of the courtroom, the study focuses on the analysis of defense lawyers question forms and functions from the pragma-dialectical discourse perspectives. The findings of the study suggest that the use of declarative question, tag question, and projection question forms are the defense lawyers’ discursive strategies to control and dominate the language of the witnesses. Such questioning forms function by potentially damaging witnesses’ admission and limiting their response boundaries and are found the influential defense lawyers’ discursive strategies through which the existing narratives of the witnesses are attacked and deconstructed.